Root colonization studies to elucidate the endophytic association of moisture stress tolerant Trichoderma isolates in black pepper (Piper nigrum L.): Endophytic association of stress tolerant Trichoderma isolates in black pepper - Vijayasanthi, K V; Anees, K; Krishnamurthy, K S; Praveena, R (Journal of Spices and Aromatic Crops, 2025)
In the present study, endophytic colonization of moisture and temperature tolerant isolates of Trichoderma viz., T. asperellum (IISR NAIMCC 0049), T. erinaceum (IISR APT1), T. harzianum (IISR APT2), T. harzianum (IISR KL3), T. lixii (IISR KA15) and T. asperellum (IISR TN3) were studied under in vitro conditions. Single node stem cuttings of black pepper (variety IISR Thevam) grown in culture bottles were inoculated with the spore suspensions of Trichoderma. Root samples were collected from treated and untreated plants at 24h, 48h, 72h, 3rd, 5th, 7th, 14th, 21st and 28th day after inoculation (DAI). During the early stages of colonization, pre-germinated conidia were abundantly observed on the root surface, subsequently, hyphae penetrated the root system. Among the six tested isolates, T. harzianum (APT2) exhibited the earliest intercellular colonization, initially observed in the cortical zone, progressively advancing to the vascular system, followed by intracellular colonization. Whereas the isolates, T. harzianum (KL3), T. erinaceum (APT1), and T. asperellum (TN3) exhibited endophytic colonization only from the 5th DAI. T. harzianum (APT2) also demonstrated the highest colonization frequency, while T. asperellum (TN3) showed the lowest. Findings of the study highlight the significant variation in root colonization capacities among moisture tolerant Trichoderma isolates. The endophytic association of these Trichoderma isolates may play a vital role in enhancing resistance to both biotic and abiotic stresses in black pepper.